TAX AVOIDANCE POTENSIAL BASED ON FINANCIAL PERFORMANCE, CSR, AND FIXED ASSET INTENSITY - TARMIDI, DEDEN; Dirman, Angela; Yudha, Fairas Panca (Berkala Akuntansi dan Keuangan Indonesia, 2025)
The study objectives to be achieved are to provide understanding and knowledge to the public, especially the government, management, investors and creditors regarding the potential for corporate tax avoidance based on financial performance, corporate social responsibility, and fixed asset intensity and can be used as a reference for further researchers and reference for stakeholders such as management, investors, creditors and the government in making relevant and reliable decisions. The study was conducted with a multiple linear regression approach in testing the hypothesis, and the data collection technique used purposive sampling method. The sample in the study is a manufacturing company in the consumer goods sector listed on the Indonesia Stock Exchange from 2018 to 2022 and has positive profits. The results showed that high corporate financial performance has the potential to minimise tax avoidance, this is because the resources owned by the company are able to encourage the company to pay taxes according to applicable regulations.. While corporate social responsibility or fixed asset intensity has no effect on tax avoidance.